Startling Discoveries and Contrarian Anomalies: Small Comets and Other Heresies: Cosmic Rain: The Controversial Discovery of Small Comets by Louis A. Frank - Bauer, Henry (Journal of Scientific Exploration, 2022)
This book should be required reading for all scholars and students of Science and Technology Studies (STS), which encompasses the history and sociology of science and the interaction of science with society as a whole.1 Anomalists will find the discovery narrative engrossing and the whole book rewarding, well worth coping with the occasional technicalities. Lay readers should likewise appreciate Part 1 and will miss little of importance to them by scanning Part 2 more rapidly. Cosmic Rain is really several books in one. Most directly, it is a fascinating scientific detective story. At the same time, as Frank recognized (p. 4), it is an important case study in the history of science, illuminating most particularly the circumstances of scientific breakthroughs that are surprising and unforeseen. Frank’s experiences illustrate several general points about the manner in which science receives—or rather, resists—startling novelty. Furthermore, this book is a very detailed first-hand description of scientific activity, warts and all, that should enable non-scientists to begin to recognize that scientific activity is very much like other human activities: influenced by human behavior and human psychology, not only by the objective technical considerations. Louis Frank was a distinguished physicist at the University of Iowa whose specialty was plasma physics. In the early 1980s, he was puzzled by persistent dark spots in ultraviolet (UV) images of the outer reaches of the Earth taken from a satellite, the Dynamics Explorer, which carried several instruments that were Frank’s responsibility.